Športna dejavnost nosečnic - Plaskan, Katja (Šport (Ljubljana), 2018)
The main aim of the research was to analyze how sportingly active or inactive women are during their pregnancy. We wanted to find out if their activity differs depending on their age and education level and in what capacity women were sportingly active before pregnancy. In research participated 44 pregnant women from different parts of Slovenia, in different age and education level. We used the statistics program SPSS with the method of frequency distribution and X2-test of independent hypothesis to analyze the data. Analyzing the data we gathered, most women are active occasionally, in disorganized form of activity; doing mostly walking and swimming. Most women who are active during their pregnancy were already sportingly active before. Frequency of activity does not depend on age or education level. The most important reasons for their inactivity prove to be various health problems and the most common reason for them being active is maintaining their health.
Keywords: izobrazba; nosečnost; starost; šport; športna dejavnost